The Operational Risk Management and Supplier Service Recovery in Improving Customer Satisfaction - Gaffar, Ichsan; Agustina, Ika; Tohiroh; Wicaksono, Adi (Yayasan Ilomata, 2024)
Currently, many production facilities are very concerned about the sustainability of their production processes. Generally, ICS users need suppliers to maintain production facilities, especially during the operation period. Therefore, response of supplier is important to recover the critical equipment of production facilities such as ICS in Indonesia. In this study, ORM (Operational Risk Management) was chosen as one of the independent variables along with Supplier Service Recovery to create customer satisfaction who do not have a service contract with the supplier. Strategy of suppliers is needed to find good after sales service. There is a research gap in this study between the expectations of ICS users and their Satisfaction without considering long-terms relationship and long term marketing /business plan. This is conducted using a quantitative approach. Data collection method is done by providing a list of questions and sent to users maintenance managers where are located with in Indonesia. The 20 questionnaires are developed according to each variable. The 5-point Likert scale is used. The tool of analyze is using the Structural Equation Model with the WarpPLS 7.0. approach. ORM is found to mediate the relationship between supplier service recovery and customer satisfaction but supplier service recovery will not give impact to customer satisfaction directly. The ORM and Supplier Service Recovery are proven to bring satisfaction to ICS customers.